Implementation of Zakat & Professional Income Tax Payments for Notaries & PPAT (Comparative Law Study of Zakat Payment System & Professional Income Tax) - Ade Adriansyah; Anis Mashdurohatun; Widhi Handoko (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to see the implementation of the Notary and PPAT professional zakat and Income Tax payment system, the reason is that the assisting system of implementing zakat and Income Tax of the Notary and PPAT profession has not met expectations and has not been able to eradicate poverty, ideal implementation of zakat and income tax notary and PPAT in the context of poverty alleviation. The approach method used in this research is the normative juridical method. The specification of this research is research with descriptive analytical breakdown specifications. Sources of research data are primary and secondary data. The data collection uses literature study as the main data and interviews as supporting data. The data analysis method used in this study is a qualitative method. The results of the study state that the implementation of the zakat and tax payment system in the stages of the notary profession and PPAT has not met expectations and has not been able to eliminate poverty because government and private ‘amil zakat institutions are still unable to collect large amounts of zakat funds. The reason the notary and PPAT professional zakat and tax payment systems have not met expectations and have not been able to incubate poverty are religious factors and non-religious factors. Ideally, the implementation of zakat and tax payments at the professional level of notaries and PPAT in the context of poverty alleviation, such as in Malaysia, taxes that have been deducted by each individual against a number of values that are not actually tax payments .